Case report: Dermatophytic pseudomycetoma in a domestic Korean short hair cat treated with intralesional injection of amphotericin B and oral terbinafine administration - Cho, Jaechun; Park, Chul; Park, Jinho; Yoon, Ji-Seon (Frontiers in Veterinary Science, 2024)
Dermatophytic pseudomycetoma (DPM), which is a deeper dermal and/or subcutaneous infection of dermatophytes, has been rarely reported in Domestic Korean Short Hair Cats. A 3-year-old, spayed female, domestic Korean Short Hair Cat presented with a history of crusts, nodules, and pruritus for 1 year. At the initial presentation, multifocal ulcerative nodules covered with yellowish grains were noted on her ventral thorax, abdomen, flank, and left hindlimb. Cytology of ulcerative nodules revealed degenerative neutrophils, macrophages, multinucleated giant cells, and hyphae. Histological examination of nodules revealed pyogranulomatous dermatitis with fungal plaques, and Microsporum canis and Staphylococcus aureus were identified in the culture. Therefore, the cat was diagnosed with DPM with secondary pyoderma. Oral itraconazole (10 mg/kg, once a day) was administered, but no significant improvement was observed. Therefore, intralesional (IL) injection of amphotericin B (0.6 mg/nodule) and oral administration of terbinafine (30 mg/kg, twice a day) were administered to the cat. With these medications, ulceration and the number and size of nodules decreased significantly, although large dome-shaped nodules remained. Skin lesions were treated with oral terbinafine and itraconazole administration for 5 months. However, after 6 months, recurrence of multifocal ulcerative nodules was observed, and the cat died 10 months after initial presentation. In this case, IL amphotericin B and oral terbinafine administration were partially effective in DPM treatment, suggesting that this may be an option for DPM treatment. Further studies to determine dose and frequency of IL amphotericin B in the management of DPM are warranted.